Self-reported incidents of violence towards nurses working in acute psychiatric units - Ntombiyakhe Bekelepi; Penelope Martin (AOSIS, 2023)
Background: Acute psychiatric units are found to be stressful working environments because of the nature of illness patients present with. Objectives: This study aimed to determine self-reported incidents of physical and verbal violence towards nurses working in acute psychiatric units in Western Cape, South Africa. Method: A questionnaire was used to collect data. Chi-square test was performed to determine association between gender, category and experience of violence. Mann-Whitney U test was carried out to determine associations between years of employment and the likelihood of experiencing physical violence and verbal abuse. Results: Overall physical violence 35 (34.3%) and verbal abuse 83 (83%) incidents. Most female respondents reported both physical violence (74.2%, n = 26) and verbal abuse (72.2%, n = 60), with (56.2%, n = 18) professional nurses reporting physical violence. Years of employment was statistically significantly associated with the likelihood of nurses experiencing physical violence (p = 0.007). Conclusion: Most respondents (74.2%, n = 26) were females and they mostly experienced physical violence and verbal abuse while 28.2% (n = 29) were males. Years of service were associated with the likelihood of experiencing physical violence. Contribution: The knowledge gained will add on existing knowledge about the challenge of violence experienced by nurses in the workplace and might have an influence on policymakers.